The Efficacy and Safety of Mirabegron for the Treatment of Neurogenic Lower Urinary Tract Dysfunction: A Systematic Review and Meta-analysis - Zhang, Dongxu; Sun, Fengze; Yao, Huibao; Bao, Xingjun; Wang, Di; Cui, Yuanshan; Wu, Jitao (Frontiers in Pharmacology, 2021)
Background and Objective: Over the past few years, mirabegron has been increasingly used as a therapeutic option for neurogenic lower urinary tract dysfunction. Here, we carried out a meta-analysis to investigate the efficacy and safety of mirabegron for the treatment of neurogenic lower urinary tract dysfunction. Methods: We used a range of databases to retrieve randomized controlled trials (RCTs) relating to mirabegron in patients with neurogenic lower urinary tract dysfunction: PubMed, Embase, and Cochrane Library; our strategy conformed to the PICOS (populations, interventions, comparators, outcomes, and study designs) strategy. Results: Our analyses involved four RCTs involving 245 patients. We found that mirabegron treatment resulted in a significant improvement in bladder compliance [mean difference (MD) = 19.53, 95% confidence interval (CI): 14.19 to 24.87, P < 0.00001], urinary incontinence episodes (MD = −0.78, 95% CI: −0.89 to −0.67, P < 0.00001) and Incontinence Quality of Life (I-QOL) (MD = 8.02, 95% CI: 3.20 to 12.84, P = 0.001). Significant differences were detected in terms of Patient Perception of Bladder Condition (PPBC) (MD = −0.54, 95% CI: −1.46 to 0.39, P = 0.26) and urinary urgency episodes (MD = −0.72, 95% CI: −3.1 to 1.66, P = 0.55). With regard to safety, there were no significant differences between mirabegron and control groups in terms of the incidence of drug-related adverse events [odds ratio (OR): 0.83, 95% CI: 0.43 to 1.59, P = 0.57], arrhythmias (OR: 1.27, 95% CI: 0.37 to 4.38, P = 0.70), hypertension (OR: 0.70, 95% CI: 0.13 to 3.82, P = 0.68), or post-voiding residual volume (MD: 1.62, 95% CI: −9.00 to 12.24, P = 0.77). Conclusion: Mirabegron is an efficacious and safe treatment for patients with neurogenic lower urinary tract dysfunction.